Arctic bramble, berry with unique aroma is a rich source of phytochemicals. Cultivation is still problematic - Kokko, Harri; Hukkanen, Anne; Kostamo, Katri; Markkula, Paavo; Kärenlampi, Sirpa (Nordic Association of Agricultural Scientists, 2007)
The main goal in the cultivation trials is the evaluation of the productivity and downy mildew resistance of a selected arctic bramble clone, which in preliminary trials has shown disease resistance.